Recent Advances in the Application of Nanozymes in Amperometric Sensors: A Review - Liu Tong; Lina Wu; Enben Su; Yan Li; Ning Gu (Chemosensors, 2023)
Amperometric sensors evaluate current changes that occur as a result of redox reactions under constant applied potential. These changes in current intensity are stoichiometrically related to the concentration of analytes. Owing to their unique features, such as fast reaction velocity, high specificity, abundant existence in nature, and feasibility to be immobilized, enzymes are widely used by researchers to improve the performance of amperometric sensors. Unfortunately, natural enzymes have intrinsic disadvantages due to their protein structures. To overcome these proteinic drawbacks, scientists have developed nanozymes, which are nanomaterials with enzymatic properties. As the result of significant advances in materiology and analytical science, great progress has been achieved in the development of nanozyme-based amperometric sensors with outstanding performance. To highlight achievements made in recent years, we first summarize the development directions of nanozyme-based amperometric sensors. Then, H2O2 sensors, glucose sensors, sensors combining natural enzymes with nanozymes, and sensors targeting untraditional specific targets will be introduced in detail. Finally, the current challenges regarding the nanozymes utilized in amperometric sensors are discussed and future research directions in this area are suggested.